HABIT TRACKER SEBAGAI MEDIA CETAK UNTUK MEMBIASAKAN AKTIVITAS PRODUKTIF SANTRIWATI DI PONDOK PESANTREN - Fadhilah Wardatul Muslimah; Joko Subando (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
Education in Islamic boarding schools (pesantren) not only focuses on religious knowledge but also emphasizes character development, especially for female students (santriwati) who carry dual responsibilities. Challenges in maintaining consistency between worship and daily productive activities often arise due to low self-awareness and lack of structured tools. This article explores the effectiveness of the Habit Tracker as a printed medium to support positive habit formation and productivity among santriwati, using behaviorist theory and Islamic values. The study adopts a library research method with a qualitative descriptive approach. The findings indicate that the Habit Tracker can help santriwati build discipline, manage their time, and enhance spiritual self-awareness in a consistent and independent manner.